A Question of Degree: The Effects of Degree Class on Labor Market Outcomes - Andy Feng; Georg Graetz (Institute for the Study of Labor (IZA), 2015)
How does measured performance at university affect labor market outcomes? We show that degree class a coarse measure of student performance used in the UK causally affects graduates' industry and hence expected wages. To control for unobserved ability, we employ a regression discontinuity design that utilizes rules governing the award of degrees. A First Class (Upper Second) increases the probability of working in a high-wage industry by thirteen (eight) percentage points, and leads to three (seven) percent higher expected wages. The results point to the importance of statistical discrimination, heuristic decision making, and luck in the labor market.
Keywords: C26; I24; J24; J31; 330; high skill wage inequality; regression discontinuity design; statistical discrimination